Acute net stress of young adult zebrafish (Danio rerio) is not sufficient to increase anxiety-like behavior and whole-body cortisol - Aponte,Amy; Petrunich-Rutherford,Maureen L. (PeerJ, 2019)
In recent years, the zebrafish (Danio rerio) has become a popular model to study the mechanisms of physiological and behavioral effects of stress, due to the similarity in neural structures and biochemical pathways between zebrafish and mammals. Previous research in this vertebrate animal model has demonstrated an increase in whole-body cortisol resulting from an acute (30-second) net handling stress, but it remains unclear whether such a stressor will concomitantly increase anxiety-like behavior. In addition, as the previous study examined the effects of this acute stressor in adult zebrafish after a brief period of isolation, it is unclear whether this stressor would be effective in eliciting cortisol increases in younger aged subjects without isolation. In the current study, young adult zebrafish (approximately 90 days post-fertilization) were briefly exposed to a net handling stressor and were subsequently subjected to either the novel tank test or the light/dark preference test. The novel tank test was used to measure exploration and habituation in response to a novel environment, and the light/dark preference test was used to measure locomotor activity and scototaxis behavior. All subjects were sacrificed 15 minutes post-stressor and were analyzed for whole-body levels of cortisol. Contrary to expectations, there was no effect of acute net handling on cortisol levels. Similarly, acute net handling did not significantly induce anxiety-like behavior during the novel tank test or the light/dark preference test. Our findings demonstrate that there are possible developmental differences in response to an acute net handling stress, as we did not observe alterations in hormonal or behavioral measures of anxiety in young adult zebrafish. Alternatively, if zebrafish are not isolated before the stressor, they may be more resilient to a brief acute stressor. These results suggest the need for a different or more intense acute stressor in order further explore neuroendocrine mechanisms and anxiety-like behavior at this developmental stage in the zebrafish animal model.
Keywords: Zebrafish; Stress; Light-dark; Novel tank; Cortisol; HPA; HPI; Anxiety; Young adult; Juvenile